Development of a point-of-care biomedical diagnostic method for blood coagulation evaluation in a drop of blood - Louka, Marinos (My University, 2019)
Blood coagulation is a defense mechanism and activated in case of blood loss due to any vessel damage or other injury. In some pathological cases the blood coagulation malfunction and the created clots grow rapidly, and as a result they may even fully block the normal blood ow. The aim of this work is to describe the coagulation and the structural properties of whole blood with the use of image processing tech- niques. Image analysis is an important tool in a di erent scienti c eld and in the industry, covering a range of applications from clinical diagnosis to robotic applica- tions. Image processing techniques were utilized by using specialized tools (Matlab) for the characterization of the blood coagulation, with the purpose of developing a diagnostic biomedical design for a Point-of-Care device. The results showed that coagulation indices can be developed based on image processing metrics. More speci cally, mean image intensity characteristics, and coagulation region analysis, show a very good sensitivity, with a great potential for a robust characterisation of coagulation.
Keywords: Blood coagulation; Image processing; Point-of-Care device